2019
DOI: 10.1007/s00425-019-03265-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of autophagy during pioneer root and stem development in Populus trichocarpa

Abstract: Main conclusion Autophagy is involved in developmentally programmed cell death and is identified during the early development of phloem, as well as xylem with a dual role, as both an inducer and executioner of cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 71 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…In Populus trichocarpa, ATG genes and the ATG8 protein are expressed at different stages during root or stem primary and secondary development. Ultrastructural observations have revealed that autophagosomes accumulate during differentiation of xylem in roots (Wojciechowska et al, 2019). These results exhibit autophagy is involved in root morphogenesis.…”
Section: The Roles Of Autophagy In Plant Root Developmentmentioning
confidence: 73%
“…In Populus trichocarpa, ATG genes and the ATG8 protein are expressed at different stages during root or stem primary and secondary development. Ultrastructural observations have revealed that autophagosomes accumulate during differentiation of xylem in roots (Wojciechowska et al, 2019). These results exhibit autophagy is involved in root morphogenesis.…”
Section: The Roles Of Autophagy In Plant Root Developmentmentioning
confidence: 73%
“…While the role of ROS and antioxidants in the lignification of tracheary elements in cell cultures and their role in xylogenesis in developing stems are well known, information is lacking on their role in developmental processes in underground organs, such as pioneer roots. Only a few recent studies have compared pioneer root development to the ontogeny of stems [31,32]. In these studies, similarities were noted in cell wall development and the PCD of xylem cells, as well as organ-specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Plants were then transferred into rhizotrons after a three-month period. Roots were grown in clear-walled chambers filled with natural soil and shoots were grown normally, as described by Wojciechowska et al [18,31].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were grown in a growth chamber (Conviron GR96) at 18 • C day/14°C night temperature and a 16 h day/8 h night photoperiod. After two months, plants were transferred to rhizotrons as described in Wojciechowska et al [95]. The material for the study was sampled during the first vegetative season at three time points based on morphological markers of senescence.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%